Evaluation of oxidative stress in severe acute malnourished children at malnutrition treatment centre of Sardar Patel Medical College, Bikaner, Rajasthan, India - Verma, Anita; Saini, Tarachand; Meena, Kuldeep (International Journal of Research in Medical Sciences, 2017)
Background:Malnutrition represents one of the most severe health problems in India. Free radicals play an important role in immunological response, which induces the oxidative surplus in severe acute malnutrition. Severe dietary deficiency of nutrients leads to increased oxidative stress in cellular compartments. The goal of this study was to evaluation of oxidative stress in severe acute malnourished children at malnutrition treatment centre of S. P. Medical College, Bikaner, Rajasthan, India. Methods: The cross sectional study was conducted after the approval of ethical committee, in the Department of Biochemistry and Paediatrics at Sardar Patel medical College of Bikaner. The present study included 100 children between the age of 6 months to 5 years with the help of Paediatrician. Serum Lipid peroxide was measured by precipitating lipoproteins with trichloroacetic acid and boiled with thiobarbituric acid which reacts with Malondialdehyde to give pink colour as per Kei satoh's method. Results: Significantly increased levels of serum malondialdehyde (p <0.001) were found in the patients as compared to those in controls. Conclusion: Deficiency of various nutrients in severe acute malnutrition leads to generation of heavy oxidative stress.